Comparison of attractants for monitoring Drosophila suzukii in sweet cherry orchards in Italy. (23rd June 2017) - Tonina, L.; Grassi, A.; Caruso, S.; Mori, N.; Gottardello, A.; Anfora, G.; Giomi, F.; Vaccari, G.; Ioriatti, C.
Abstract: The invasiveness of Drosophila suzukii Matsumura is causing sizable damage to soft fruits and cherry. In order to define a targeted strategy for D. suzukii management, it is important to have access to highly sensitive trapping tools for detection, monitoring and control that are also selective, practical in use, economic, and with low environmental impact. The aim of this study was to compare different combinations of traps and lures to define a best practice approach for D. suzukii monitoring in Italy, extended over a wide elevational gradient and landscape complexity. The high attractiveness was not always combined with high selectivity, as in some cases up to 95% of the Drosophila spp. captured were belonging to species different from D. suzukii . The commercial Droso‐Trap was very efficient providing high capture ability. Overall, the most attractive lure was Droskidrink while Suzukii Trap was the most selective one. Lure attractiveness and selectivity, however, changed during the season in relation to environmental temperatures and phenological developmental stages, suggesting the need for implementing different lures in different periods and for the different purposes (monitoring or mass trapping). In terms of trap management, Droskidrink showed the problem of bacterial‐gel formation, while Suzukii Trap and Pherocon SWD were easier to handle as they did not need to be checked at weekly interval. Finally, these results were gathered to convey the most efficient combination of trap and bait able to efficiently perform mass trapping and attract and kill technique.